2010
DOI: 10.1016/j.snb.2010.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of F doping on TiO2 acidic sites and their application in QCM based gas sensors

Abstract: a b s t r a c tTitanium dioxide (TiO 2 ) and fluorine doped titanium dioxide (F-TiO 2 ) particles were prepared by a onepot hydrothermal synthesis, and applied on quartz crystal microbalance (QCM) resonators to detect trace levels of nerve agent stimulant, dimethyl methylphosphonate (DMMP). DMMP sensing measurements exhibited that TiO 2 functionalized QCM resonators had fast response and recovery as well as satisfactory sensitivity. F-TiO 2 functionalized QCM resonators showed even faster response and higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…F:TiO 2 thin‐films have mostly been synthesized by sol‐gel, hydrothermal, and physical vapor deposition (PVD) routes . Interestingly, thin‐films of F:TiO 2 have not previously been grown by chemical vapor deposition (CVD) and in this article we demonstrate the first such case at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…F:TiO 2 thin‐films have mostly been synthesized by sol‐gel, hydrothermal, and physical vapor deposition (PVD) routes . Interestingly, thin‐films of F:TiO 2 have not previously been grown by chemical vapor deposition (CVD) and in this article we demonstrate the first such case at atmospheric pressure.…”
Section: Introductionmentioning
confidence: 82%
“…The mode of enhancement has been attributed to a red‐shifted bandgap, the creation of surface oxygen vacancies, the enhancement of surface acidity and the increase of Ti 3+ states . The gas sensing and optical properties of F:TiO 2 thin‐films have also been studied. Recently, it has also been shown that electrical resistivities (ρ = 1.6 × 10 −3 Ω cm) not far from fluorine doped tin oxide (ρ ≈ 5–6 × 10 −4 Ω cm can be achieved in F:TiO 2 thin‐films grown by an optimized physical layer deposition (PLD) process …”
Section: Introductionmentioning
confidence: 99%
“…In the meanwhile, the sensing performance of metal oxide nanomaterials can be improved by either doping or preparing solid solutions [6,[72][73][74][75]. The effect of Zn-doping on the sensitivity of In 2 O 3 nanowires was investigated towards different gases, such as carbon monoxide (CO), NO 2 , ethanol, and H 2 [73].…”
Section: Improvement Of Sensing Performance Including the Operating Tmentioning
confidence: 99%
“…In particular, the sensor was shown to be effective in the detection of the nerve agent dimethyl methylphosphonate. Other studies investigating the detection of dimethyl methylphosphonate used nickel and zinc phthalocyanine surfaces with detection limits as low as 100 parts per billion (Tasaltin et al ., ), titanium dioxide based particles (Zhao et al ., ) and a ZnO/MnO 2 surface (Pei et al ., ). Furthermore, dimethyl methylphosphonate was detected on new synthetic polymers, with a hybrid organic/inorganic polymer displaying the best stability whereas an epoxy resin surface showed the best initial sensitivity (Maji et al ., ).…”
Section: Small Molecule Interactionsmentioning
confidence: 99%